Design of Motivational-Realistic-Pancasila Learning in Mathematics - Marup, Marup; Tahmir, Suradi; Talib, Ahmad; Kamaruddin, Nurzatulshima (Sekolah Pascasarjana Universitas Negeri Malang (UM), 2024)
Learning mathematics in class greatly influences students' learning success both in terms of knowledge and attitudes. In carrying out learning, a learning design is needed that can foster student motivation so that they provide learning outcomes to the learning objectives. Motivational-Realistic-Pancasila learning design is considered to be an alternative solution. Morela is a design that combines motivational, realistic indicators and Pancasila values. The teaching of mathematics in the classroom significantly influences students' academic success, both in terms of knowledge and attitude. To effectively carry out the teaching process, a well-designed instructional approach is necessary to foster students' motivation to achieve learning outcomes in line with the educational objectives. The Morela design is considered one alternative solution, as it integrates indicators of motivation, realism, and Pancasila values.DOI: 10.17977/jps.v12i42024p160